Learning and living God’s story: The power of liturgy for, with, and through people with disabilities - Scheuermann, Rochelle (Missiology, 2024)
Liturgy is an embodied means of participating in God’s story of salvation. Through a tradition of prayers, hymns, and sacraments, God’s story is experienced through the senses as people receive, give, and share in acts of listening, proclaiming, and enactment. Robert Webber argues that participation in liturgy is itself a means for evangelization. Through liturgy, the church lives out God’s story while also shaping participants to know God and in turn live out God’s story in the world. For people with disabilities, particularly intellectual and developmental disabilities, liturgy helps to form Christ followers through expressive means like repetition, song, and bodily movement. While this is often seen as a one-way movement to people with disabilities, liturgy is quite literally the work of the people. Through their participation in liturgy, people with disabilities contribute to the church’s witness and to the embodiment of God’s story, challenging ableism and contributing to works of justice and goodness.